A quantitative assessment of rockfall influence on forest structure in the Swiss Alps - Christine Moos; Nora Khelidj; Antoine Guisan; Heike Lischke; Christophe F. Randin (European Journal of Forest Research, 2021)
Forests below rocky cliffs often play a very important role in protecting settlements against rockfall. The structure and development of these forests are expected to be substantially affected by the disturbance of the falling rocks. Knowing about this effect is important to predict the development of protection forests and consider potential effects of the falling blocks in management strategies. The goal of this study is to quantify differences in forest structure depending on rockfall activity in four different sites in the Swiss Alps. For this, we collected data on forest structure in zones of different rockfall activity and derived rockfall impact probabilities based on rockfall simulations. We assessed whether differences in forest structure and signs of rockfall disturbance could be observed between the rockfall zones. We additionally built mixed-effects models to identify the key variables explaining the forest characteristics described by diameter (DBH) and basal area (bA). The forest structure differs between the rockfall zones, however, with varying effects amongst the sites. DBH tends to decrease with increasing rockfall activity, whereas tree density appears to be little impacted by rockfall. For most sites, the number of deposited blocks and the simulated tree impact probability have a significant effect in the models along with the species, whereas for one site, hardly any effect of rockfall was found. Our results, obtained either from direct measurements or modelling, show that rockfall can locally influence the structure of forests, whereas the influence depends on the frequency and intensity of the rockfall disturbance. Impact probabilities obtained by simulations can serve as a good proxy for rockfall disturbances.

Topo‐climatic microrefugia explain the persistence of a rare endemic plant in the Alps during the last 21 millennia - Theofania S. Patsiou; Elena Conti; Niklaus E. Zimmermann; Spyros Theodoridis; Christophe F. Randin (Global Change Biology, 2014)
Ongoing rapid climate change is predicted to cause local extinction of plant species in mountain regions. However, some plant species could have persisted during Quaternary climate oscillations without shifting their range, despite the limited evidence from fossils. Here, we tested two candidate mechanisms of persistence by comparing the macrorefugia and microrefugia ( MR ) hypotheses. We used the rare and endemic Saxifraga florulenta as a model taxon and combined ensembles of species distribution models ( SDM s) with a high‐resolution paleoclimatic and topographic dataset to reconstruct its potential current and past distribution since the last glacial maximum. To test the macrorefugia hypothesis, we verified whether the species could have persisted in or shifted to geographic areas defined by its realized niche. We then identified potential MR based on climatic and topographic properties of the landscape and applied refined scenarios of MR dynamics and functions over time. Last, we quantified the number of known occurrences that could be explained by either the macrorefugia or MR model. A consensus of two or three SDM techniques predicted absence between 14–10, 3–4 and 1 ka bp , which did not support the macrorefugia model. In contrast, we showed that S. florulenta could have contracted into MR during periods of absence predicted by the SDM s and later re‐colonized suitable areas according to the macrorefugia model. Assuming a limited and realistic seed dispersal distance for our species, we explained a large number of the current occurrences (61–96%). Additionally, we showed that MR could have facilitated range expansions or shifts of S. florulenta . Finally, we found that the most recent and the most stable MR were the ones closest to current occurrences. Hence, we propose a novel paradigm to explain plant persistence by highlighting the importance of supporting functions of MR when forecasting the fate of plant species under climate change.

Spring frost and growing season length co‐control the cold range limits of broad‐leaved trees - Chris Kollas; Christian Körner; Christophe F. Randin (Journal of Biogeography, 2014)
Aim The aim of this study was to test, based on biological theory, which facet of temperature is most closely associated with the elevational and latitudinal low‐temperature limits of seven European broad‐leaved tree species. We compared three temperature‐related potential constraints across three study regions: (1) absolute minimum temperature within 100 years; (2) lowest temperatures during the period of bud‐break; and (3) length and temperature of the growing season. Location Western and Eastern Swiss Alps (1165–2160 m a.s.l.) and southern Sweden (57° N–59° N). Methods In situ temperature was recorded at the high‐elevation and high‐latitude limits of seven broad‐leaved tree species and correlated with temperatures at the nearest weather stations, in order to reconstruct the temperature regime for the past 50 years. By applying generalized extreme value distribution theory, we estimated the lowest temperatures recurring during the life span of a tree. Results At their high‐elevation limits, five out of the seven tree species experienced winter minimum temperatures considerably warmer than their known maximum freezing resistance in winter. For the bud‐break period, potentially damaging temperatures occurred at both the elevational and the latitudinal limits and for all four species for which phenological data were available. Three out of five species for which a latitudinal replicate was available showed a similar length of growing season at their respective elevational and latitudinal limits. The mean temperature during the growing season was always warmer at a species’ latitudinal limit than at its elevational limit, and hence this variable does not bear general explanatory power for the range limit. Main conclusions Low‐temperature extremes during bud‐break are the most likely candidates for controlling the elevational and latitudinal limits of broad‐leaved tree species. The absolute minimum temperature in winter and the mean temperature during the growing season are unlikely to constrain the cold limits of these species. Thus, the results call for the use of temperature data (extremes) during key stages of spring phenology when attempting to explain the low‐temperature range limits and to predict the potential range shifts of deciduous tree species.

Working toward integrated models of alpine plant distribution - Bradley Z. Carlson; Christophe F. Randin; Isabelle Boulangeat; Sébastien Lavergne; Wilfried Thuiller; Philippe Choler (Alpine Botany, 2013)

Do the elevational limits of deciduous tree species match their thermal latitudinal limits? - Christophe F. Randin; Jens Paulsen; Yann Vitasse; Chris Kollas; Thomas Wohlgemuth; Niklaus E. Zimmermann; Christian Körner (Global Ecology and Biogeography, 2013)
Aim We compared the upper limits of 18 deciduous tree species with respect to elevation in S witzerland and latitude in E urope. We hypothesized that species would exhibit the same relative positions along elevation and latitude, which can be expected if species have reached their thermal cold limit along both gradients. Location E urope and S witzerland. Methods We developed a method to identify a least biased estimate of the elevational and latitudinal cold temperature limits of species and for comparing the relative rank positions with respect to these two limits. We applied an algorithm to calculate the elevation of the potential tree line for each point in the gridded landscape of E urope and S witzerland. For each occurrence of each species, the elevation was extracted from digital elevation models. The vertical distance between the elevation of the potential regional climatic tree line and the uppermost species occurrences was calculated and used for comparisons between elevation and latitude. Results We found a strong relationship between the thermal latitudinal and elevational distances of species’ cold limits to the potential tree line, with only marginally significantly different rank positions ( P = 0.057) detected along elevational and latitudinal gradients. A first group of nine species showed very similar thermal distances to the potential tree lines along elevation and latitude. Among these species, eight showed a significant decrease in their elevational limit towards high latitudes across mountainous regions of E urope. A second group of seven species occupied a climatic niche closer to the tree line at the edge of their latitudinal range, and only two species did not fill their thermal niche. Main conclusions Our study provides support for the common concept of a species range–environment equilibrium. Notably, we did not detect a stronger deviation for the filling of thermal niches at latitudinal limits compared with elevational limits, although the former involves a species covering a much greater geographic distance.

Thermal niches are more conserved at cold than warm limits in arctic‐alpine plant species - Loïc Pellissier; Kari Anne Bråthen; Pascal Vittoz; Nigel G. Yoccoz; Anne Dubuis; Eliane S. Meier; Niklaus E. Zimmermann; Christophe F. Randin; Wilfried Thuiller; Luc Garraud; Jérémie Van Es; Antoine Guisan (Global Ecology and Biogeography, 2013)
Aim Understanding the stability of realized niches is crucial for predicting the responses of species to climate change. One approach is to evaluate the niche differences of populations of the same species that occupy regions that are geographically disconnected. Here, we assess niche conservatism along thermal gradients for 26 plant species with a disjunct distribution between the A lps and the A rctic. Location E uropean A lps and N orwegian F innmark. Methods We collected a comprehensive dataset of 26 arctic‐alpine plant occurrences in two regions. We assessed niche conservatism through a multispecies comparison and analysed species rankings at cold and warm thermal limits along two distinct gradients corresponding to (1) air temperatures at 2 m above ground level and (2) elevation distances to the tree line ( TLD ) for the two regions. We assessed whether observed relationships were close to those predicted under thermal limit conservatism. Results We found a weak similarity in species ranking at the warm thermal limits. The range of warm thermal limits for the 26 species was much larger in the Alps than in Finnmark. We found a stronger similarity in species ranking and correspondence at the cold thermal limit along the gradients of 2‐m temperature and TLD . Yet along the 2‐m temperature gradient the cold thermal limits of species in the Alps were lower on average than those in Finnmark. Main conclusion We found low conservatism of the warm thermal limits but a stronger conservatism of the cold thermal limits. We suggest that biotic interactions at the warm thermal limit are likely to modulate species responses more strongly than at the cold limit. The differing biotic context between the two regions is probably responsible for the observed differences in realized niches.

Using Life Strategies to Explore the Vulnerability of Ecosystem Services to Invasion by Alien Plants - Joana R. Vicente; Ana T. Pinto; Miguel B. Araújo; Peter H. Verburg; Angela Lomba; Christophe F. Randin; Antoine Guisan; João P. Honrado (Ecosystems, 2013)

Disentangling the effects of global climate and regional land-use change on the current and future distribution of mangroves in South Africa - Katrien Quisthoudt; Janine Adams; Anusha Rajkaran; Farid Dahdouh-Guebas; Nico Koedam; Christophe F. Randin (Biodiversity and Conservation, 2013)

Elevational adaptation and plasticity in seedling phenology of temperate deciduous tree species - Yann Vitasse; Günter Hoch; Christophe F. Randin; Armando Lenz; Chris Kollas; J. F. Scheepens; Christian Körner (Oecologia, 2013)

The accuracy of plant assemblage prediction from species distribution models varies along environmental gradients - Julien Pottier; Anne Dubuis; Loïc Pellissier; Luigi Maiorano; Leila Rossier; Christophe F. Randin; Pascal Vittoz; Antoine Guisan (Global Ecology and Biogeography, 2013)
Aim Climatic niche modelling of species and community distributions implicitly assumes strong and constant climatic determinism across geographical space. We tested this assumption by assessing how stacked‐species distribution models ( S ‐ SDMs ) perform for predicting plant species assemblages along elevation gradients. Location The western S wiss A lps. Methods Using robust presence–absence data, we first assessed the ability of topo‐climatic S ‐ SDMs to predict plant assemblages in a study area encompassing a 2800‐m wide elevation gradient. We then assessed the relationships among several evaluation metrics and trait‐based tests of community assembly rules. Results The standard errors of individual SDMs decreased significantly towards higher elevations. Overall, the S ‐ SDM overpredicted far more than they underpredicted richness and could not reproduce the humpback curve along elevation. Overprediction was greater at low and mid‐range elevations in absolute values but greater at high elevations when standardized by the actual richness. Looking at species composition, overall prediction success, kappa and specificity increased with increasing elevation, while the Jaccard index and sensitivity decreased. The best overall evaluation – as driven by specificity – occurred at high elevation where species assemblages were shown to be subject to significant environmental filtering of small plants. In contrast, the decreased overall accuracy in the lowlands was associated with functional patterns representing any type of assembly rule (environmental filtering, limiting similarity or null assembly). Main conclusions We provide a thorough evaluation of S ‐ SDM emphasizing the need to carefully interpret standard evaluation metrics, which reflect different aspects of assemblage predictions. We further reported interesting patterns of change in S ‐ SDM errors with changes in assembly rules along elevation. Yet, significant levels of assemblage prediction errors occurred throughout the gradient, calling for further improvement of SDMs , e.g. by adding key environmental filters that act at fine scales and developing approaches to account for variations in the influence of predictors along environmental gradients.

Temperature variation among mangrove latitudinal range limits worldwide - Katrien Quisthoudt; Nele Schmitz; Christophe F. Randin; Farid Dahdouh-Guebas; Elisabeth M. R. Robert; Nico Koedam (Trees, 2012)

Tree recruitment of European tree species at their current upper elevational limits in the Swiss Alps - Yann Vitasse; Günter Hoch; Christophe F. Randin; Armando Lenz; Chris Kollas; Christian Körner (Journal of Biogeography, 2012)
Aim The physical and physiological mechanisms that determine tree‐line position are reasonably well understood, but explanations for tree species‐specific upper elevational limits below the tree line are still lacking. In addition, once these uppermost positions have been identified, questions arise over whether they reflect past expansion events or active ongoing recruitment or even upslope migration. The aims of this study were: (1) to assess current tree recruitment near the cold‐temperature limit of 10 major European tree species in the Swiss Alps, and (2) to rank species by the extent that their seedlings and saplings exceed the elevational limit of adult trees, possibly reflecting effects of the recent climate warming. Location Western and eastern Alps of Switzerland. Methods For each species, occurrences were recorded along six elevational transects according to three size classes from seedlings to adult trees in 25‐m‐elevation steps above and below their regional upper elevational limit. Two methods were used to compare upper elevational limits between seedlings, saplings and adults within species. First, we focused on the uppermost occurrence observed in each life stage for a given species within each studied region; and second, we predicted their upper distribution range using polynomial models fitted to presence/absence data. Results Species exhibited a clear ranking in their elevational limit. Regional differences in species limits (western versus eastern Swiss Alps) could largely be attributed to regional differences in temperature. Observed and predicted limits of each life stage showed that all species were represented by young individuals in the vicinity of the limit of adult trees. Moreover, tree recruitment of both seedlings and saplings was detected and predicted significantly beyond adult tree limits in most of the species. Across regions, seedlings and saplings were on average found at elevations 73 m higher than adult trees. Main conclusions Under current conditions, neither seed dispersal nor seedling establishment constitutes a serious limitation of recruitment at the upper elevational limits of major European trees. The recruits found beyond the adult limits demonstrate the potential for an upward migration of trees in the Alps in response to ongoing climate warming.

Where will conflicts between alien and rare species occur after climate and land-use change? A test with a novel combined modelling approach - Joana Vicente; Christophe F. Randin; João Gonçalves; Marc J. Metzger; Ângela Lomba; João Honrado; Antoine Guisan (Biological Invasions, 2011)

Climate change and plant distribution: local models predict high‐elevation persistence - CHRISTOPHE F. RANDIN; ROBIN ENGLER; SIGNE NORMAND; MASSIMILIANO ZAPPA; NIKLAUS E. ZIMMERMANN; PETER B. PEARMAN; PASCAL VITTOZ; WILFRIED THUILLER; ANTOINE GUISAN (Global Change Biology, 2009)
Mountain ecosystems will likely be affected by global warming during the 21st century, with substantial biodiversity loss predicted by species distribution models (SDMs). Depending on the geographic extent, elevation range, and spatial resolution of data used in making these models, different rates of habitat loss have been predicted, with associated risk of species extinction. Few coordinated across‐scale comparisons have been made using data of different resolutions and geographic extents. Here, we assess whether climate change‐induced habitat losses predicted at the European scale (10 × 10′ grid cells) are also predicted from local‐scale data and modeling (25 m × 25 m grid cells) in two regions of the Swiss Alps. We show that local‐scale models predict persistence of suitable habitats in up to 100% of species that were predicted by a European‐scale model to lose all their suitable habitats in the area. Proportion of habitat loss depends on climate change scenario and study area. We find good agreement between the mismatch in predictions between scales and the fine‐grain elevation range within 10 × 10′ cells. The greatest prediction discrepancy for alpine species occurs in the area with the largest nival zone. Our results suggest elevation range as the main driver for the observed prediction discrepancies. Local‐scale projections may better reflect the possibility for species to track their climatic requirement toward higher elevations.

Prediction of plant species distributions across six millennia - Peter B. Pearman; Christophe F. Randin; Olivier Broennimann; Pascal Vittoz; Willem O. van der Knaap; Robin Engler; Gwenaelle Le Lay; Niklaus E. Zimmermann; Antoine Guisan (Ecology Letters, 2008)
The usefulness of species distribution models (SDMs) in predicting impacts of climate change on biodiversity is difficult to assess because changes in species ranges may take decades or centuries to occur. One alternative way to evaluate the predictive ability of SDMs across time is to compare their predictions with data on past species distributions. We use data on plant distributions, fossil pollen and current and mid‐Holocene climate to test the ability of SDMs to predict past climate‐change impacts. We find that species showing little change in the estimated position of their realized niche, with resulting good model performance, tend to be dominant competitors for light. Different mechanisms appear to be responsible for among‐species differences in model performance. Confidence in predictions of the impacts of climate change could be improved by selecting species with characteristics that suggest little change is expected in the relationships between species occurrence and climate patterns.

Are niche‐based species distribution models transferable in space? - Christophe F. Randin; Thomas Dirnböck; Stefan Dullinger; Niklaus E. Zimmermann; Massimiliano Zappa; Antoine Guisan (Journal of Biogeography, 2006)
Aim To assess the geographical transferability of niche‐based species distribution models fitted with two modelling techniques. Location Two distinct geographical study areas in Switzerland and Austria, in the subalpine and alpine belts. Methods Generalized linear and generalized additive models (GLM and GAM) with a binomial probability distribution and a logit link were fitted for 54 plant species, based on topoclimatic predictor variables. These models were then evaluated quantitatively and used for spatially explicit predictions within (internal evaluation and prediction) and between (external evaluation and prediction) the two regions. Comparisons of evaluations and spatial predictions between regions and models were conducted in order to test if species and methods meet the criteria of full transferability. By full transferability, we mean that: (1) the internal evaluation of models fitted in region A and B must be similar; (2) a model fitted in region A must at least retain a comparable external evaluation when projected into region B, and vice‐versa; and (3) internal and external spatial predictions have to match within both regions. Results The measures of model fit are, on average, 24% higher for GAMs than for GLMs in both regions. However, the differences between internal and external evaluations (AUC coefficient) are also higher for GAMs than for GLMs (a difference of 30% for models fitted in Switzerland and 54% for models fitted in Austria). Transferability, as measured with the AUC evaluation, fails for 68% of the species in Switzerland and 55% in Austria for GLMs (respectively for 67% and 53% of the species for GAMs). For both GAMs and GLMs, the agreement between internal and external predictions is rather weak on average (Kulczynski's coefficient in the range 0.3–0.4), but varies widely among individual species. The dominant pattern is an asymmetrical transferability between the two study regions (a mean decrease of 20% for the AUC coefficient when the models are transferred from Switzerland and 13% when they are transferred from Austria). Main conclusions The large inter‐specific variability observed among the 54 study species underlines the need to consider more than a few species to test properly the transferability of species distribution models. The pronounced asymmetry in transferability between the two study regions may be due to peculiarities of these regions, such as differences in the ranges of environmental predictors or the varied impact of land‐use history, or to species‐specific reasons like differential phenotypic plasticity, existence of ecotypes or varied dependence on biotic interactions that are not properly incorporated into niche‐based models. The lower variation between internal and external evaluation of GLMs compared to GAMs further suggests that overfitting may reduce transferability. Overall, a limited geographical transferability calls for caution when projecting niche‐based models for assessing the fate of species in future environments.